Instructions between the field and the lab: collecting blood for the ‘Serological Museum’ in the 1950s - Gisler, Priska (Museum and Society, 2015)
In a Science article published in 1953, Alan Boyden, a zoologist from Rutgers University and a pioneer in systematic serology, gave precise instructions on how to sample animal blood for the tissue collection that he housed in the Serological Museum. His instructions can be read as a ‘prospective account’ indicating the decisive shift in the history of the biological sciences towards the molecular level. It will be argued that Boyden’s narrative points to some of the ambiguities that marked the changing relations between the field and the lab at the time. They were connected to the kind of actors involved in collecting, the objects that were assembled, the collecting practices and the role of the museum itself. It becomes clear that the Museum was to serve as a significance converter, opening novel avenues that contributed to turning the field into a resource for the laboratory as well as helping to ease the distance between the two.